2011
DOI: 10.1099/vir.0.032581-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection induces the expression of amphiregulin, a factor related to the activation of cellular survival pathways and required for efficient viral assembly

Abstract: Amphiregulin (AREG) is a ligand of the epidermal growth factor (EGF) receptor and may play a role in the development of cirrhosis and hepatocellular carcinoma in patients infected with hepatitis C virus (HCV). AREG showed an enhanced expression in HCV-infected human hepatoma cells according to gene array analysis. Therefore, we addressed the question about the role of AREG in HCV infection. AREG expression level was elevated in hepatoma cells containing a subgenomic HCV replicon or infected by HCV. Using a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
(42 reference statements)
1
31
0
Order By: Relevance
“…Previous studies have shown that HCV infection modulates the expression of host genes. Some genes, such as the amphiregulin (AREG) gene, are required for HCV replication (54). A comparison of the transcriptomes of HCV-infected Huh7.5.1 cells with that of the uninfected control revealed that PLA2G4C expression was enhanced approximately 10-fold in JFH-1-infected Huh7.5.1 cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that HCV infection modulates the expression of host genes. Some genes, such as the amphiregulin (AREG) gene, are required for HCV replication (54). A comparison of the transcriptomes of HCV-infected Huh7.5.1 cells with that of the uninfected control revealed that PLA2G4C expression was enhanced approximately 10-fold in JFH-1-infected Huh7.5.1 cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The JFH1-HA virus with a hemagglutinin (HA) epitope at the N terminus of NS2 was constructed as previously described (15). The viral titer in the culture supernatants and cell lysates was determined by a modified endpoint dilution assay as previously described (30,34).…”
Section: Methodsmentioning
confidence: 99%
“…Huh7.5.1 cells (kindly provided by Frank Chisari) and Huh7 cells were cultured in Dulbecco's modified Eagle medium (DMEM) (Invitrogen) supplemented with 2 mM L-glutamine, nonessential amino acids, and 10% fetal bovine serum (FBS) (Invitrogen). The subgenomic HCV replicon cell lines (Huh7.5.1-SGR [30] and Con1 [34] containing subgenomic genotype 2a and 1b HCV, respectively) were grown in the same medium supplemented with 500 g ml Ϫ1 G418. Virus production.…”
Section: Methodsmentioning
confidence: 99%
“…The mixtures were centrifuged, washed with IP buffer four times, denatured by boiling in SDS-PAGE sample buffer for 5-10 min, and subjected to SDS-PAGE. Immunoblot (IB) analysis was performed as previously described (35). An Ultra ECL kit, Western Lightning Ultra, was purchased from PerkinElmer.…”
Section: Immunoprecipitation Coimmunoprecipitation and Immunoblot Amentioning
confidence: 99%